Manfaat Yoga Online bagi Remaja Putri dalam Meningkatkan Emosi Positif pada Pembelajaran Tatap Muka - Sindhu, Pujiastuti; Abidin, Zainal (Universitas Muhammadiyah Metro, 2023)
Entering the odd semester of the 2021/2022 academic year, middle school (SMP) students begin offline school (PTM) after more than one year of distant learning (PJJ) due to covid19. This study aims to explore the understanding of the benefits of yoga among young adolescent girls returning to school after pandemic. The participants were three seventh graders, age 13 years old, asked to participate in the entire process of research including four (4) teen yoga sessions and semi-structured interviews, all conducted online. Qualitative data were obtained from interview transcripts. The results showed that participants perceived the benefits of yoga in increasing positive emotions, decreasing negative emotions, and improving sleep quality and their social relationship. Research limitations in the form of problems with internet connectivity and lack of research time are also discussed. Further research has been proposed to explore the benefits of yoga for the early teen.